Institutional Collaboration on the Lake of Bakuok in Sustainable Management - Afrizal Afrizal; Mayarni Mayarni; Mimin Sundari Nasution (Iapa Proceedings Conference, 2019)
Lake Bakuok is a conservation area and traditional indigenous Lake or prohibition hole that has culture-based fishing activities, we can see this with the tradition of fishing together using nets that have become tourist destinations in Kampar Regency, Riau Province, in regional languages locally called "Ma'awuo". All activities carried out in this Bakuok lake is controlled by traditional authorities Kenegrian Tambang which has the same vision in the conservation and protection of the lake region. On the other side ecologically Bakuok lake is very alarming, with palm trees and rubber were planted alongside the lake, and the fish cages. Based on the rules regarding the ban on Lake Bakuok, not all of these rules are implemented and implemented properly, even though there are already those who supervise, there are still violations that occur. The number of institutions involved in the development of Lake Bakuok so far is still temporal or temporary, and runs each and has not formed a systematic collaboration. This study aims to see how institutional collaboration in Lake Bakuok sustainable management. The study uses qualitative research methods that aim to obtain a holistic picture of a phenomenon in the Bakuok Lake. The results showed several important items related to Lake Bakuok institutional collaboration, namely the type of network structured (network structure) that is still unclear and does not have a unified conceptual description of Lake management. The absence of Commitment to a common purpose. Trust among stakeholders is still lacking. The unavailability of standard provisions for clear procedures and responsibilities in the relevant institutions. Access to information of stakeholders who are not members as long as they can be accepted by all parties is still difficult.